Blood lead levels in relation to smoking and chronic obstructive pulmonary disease (COPD): a study from Korean National Health and Nutrition Examination Survey (KNHANES) - Lee, Eunyoung (J Thorac Dis, 2020)
BACKGROUND: Lead exposure is a resurgent environmental issue globally. Smoking can be a source of lead exposure, although the majority of lead poisonings originate from workplace exposures. However, no study has been undertaken concerning the blood lead levels based on the chronic obstructive pulmonary disease (COPD), smoking status, and other risk factors of COPD. This cross-sectional study was conducted to investigate the blood lead levels according to COPD and clinical variables associated with COPD. METHODS: Data (total number =53,829) were collected from the Korean National Health and Nutrition Examination Survey (IV in 2008 and 2009, V in 2010–2012, and VI in 2013). Multivariable linear regression analyses were performed to determine variables associated with elevated blood lead levels. RESULTS: Univariate regression analysis showed that male sex, older age, smoking, occupation level, income level, education level, and presence of COPD were related to higher blood lead levels, whereas the other co-morbidities including diabetes, hypertension, cerebral stroke, osteoporosis, asthma, and depression were not related (P<0.05). Multivariable regression analysis demonstrated that older age, male sex, smoking, occupation, and education level were independently associated with higher blood lead levels (P<0.05). CONCLUSIONS: Smoking status, occupation, and education level along with old age and male sex were independently associated with higher blood lead levels; however, COPD was not after adjustment of all confounding factors.